Problems and Countermeasures of State-owned Assets Management in Administrative Institutions - Chen, Yue (Journal of Theory and Practice of Management Science, 2023)
Fixed assets are essential basic material elements for administrative institutions to carry out business activities, and also one of the important resources for the survival and development of administrative institutions. How to do a good job of fixed assets management scientifically and effectively, ensure its safety and integrity, give full play to its efficiency, to improve the social and economic benefits of the unit, enhance the competitiveness of the unit, to build a conservation-oriented society, is undoubtedly very important. Through in-depth analysis of the problems existing in the management of fixed assets of public institutions, this paper proposes ft's opinions and suggestions to solve the problems, and then makes further analysis and demonstration by using cases.